PERBANDINGAN NILAI KETANGGUHAN DESA PESISIR ATAS RISIKO TSUNAMI DAN FAKTOR PERUBAHAN NILAI KETANGGUHAN: STUDI ATAS DESA PARANGTRITIS DAN DESA TIRTOHARGO, KABUPATEN BANTUL - Yugyasmono; Gandar Mahojwala; Eko Teguh Paripurno; Purbudi Wahyuni (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2023)
The southern coast of Java Island is a tsunami-prone area, and this condition has encouraged resilience assessment efforts carried out since 2019 by BNPB to test the resilience of villages, specifically in the event of a tsunami disaster. Like other areas on the southern coast of Java Island, Bantul Regency is at high risk, as are Parangtritis Village and Tirtohargo Village. These two villages were purposively chosen for comparison because both villages have the same high level of risk. This research aims to compare the resilience values ​​of the two villages based on assessments in 2019 and 2020 using the Village/District Disaster Resilience Assessment tool, as well as qualitatively exploring the factors that influence the resilience values ​​and changes in the resilience values ​​of the two villages. This study uses a qualitative method. Comparison of resilience values ​​is presented with narratives and comparison tables based on existing components, and exploration is explored through in-depth interviews with parties who help build resilience in the village. The results show that comparing values decreased the resilience value in Parangtritis Village from the Main Resilient Village category to the Middle Resilient Village. At the same time, there was an increase in Tirtohargo Village from the Middle Resilient Village category to the Main Resilient Village. Toughness, which is both above average, is influenced by experiences and lessons learned from the 2006 Earthquake, the strong values ​​of cooperation and independence, community initiatives through the Village DRR Forum, the role of village government, support from regional and central governments, contributions from non-government organizations, and the availability of village budgets. This research notes that enforcing assessment procedures and understanding assessment for facilitators and participants also influence the resulting value changes.